Effectiveness of the Quality Improvement Program (QIP) Implemented in Superspeciality Hospitals - Roopashree M. Rangyyan, Shrikrishna Dhale, Tamoy Saha, Ronit Mondal (International Journal of Modern Agriculture, 2020)
Introduction: The medication tracker sheet documentation with time intervals between the activities can provide vital information regarding the time delay aspects during the clinical care processes. A gap seen between the actual quality of service delivered and the expected quality of service delivery in terms of time and accuracy of documents. Closure of the gap was initiated by innovative and team in-built strategies. Objectives: To streamline and implement the medication turnaround time tracker sheet for the in-patient ward area. The medication errors were minimized. The documentation process is monitored regularly in a conducive manner for accuracy and effectiveness. Methods: The random sample size of 40 patients was determined to be tracked on each floor area. For the ease of staff who were working, every 3rd patient was selected for tracking. Process improvisation was the strategy incorporated for betterment. The average mean time was calculated. The Student T-test was incorporated to understand whether the process was statistically significant. Results and discussion: As we have two independent samples taken before and after the implementation of quality improvement program, for the statically significant results, the unpaired form of the t-test was incorporated. There is a significant difference between the meantime of pre-QIP and post-QIP. Application: Betterment Process flow from indenting of the drugs and medication along with consumables till administration of medications were streamlined. Conclusion: The importance of administering the drugs at the right time and in the right way was executed to the patients. Documentation was accurate and timelines maintained.